2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23837
|View full text |Cite
|
Sign up to set email alerts
|

Developing Courseware for Robotics in Pre-engineering Education for High School Students

Abstract: Incorporating robotics into the STEM initiative is an essential part of keeping students relevant and competitive in a global economy. This paper presents an original way of developing courseware for an introductory Robotics course as part of a six-week pre-college engineering summer program. The goal of the course was to expose high school students to Robotics engineering and involve the students in robot designing and building, programming and troubleshooting, collaborative writing, and presentation. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Mathematical formulations and explanations were also provided to give students an understanding of the concepts and principles that were necessary for creating these designs. [2] After the mechanical segment of the summer program, students were introduced to robot sensors, sensor implementation and calibration. The sensors covered included the ultrasonic, shaft encoder, touch, line tracking, vision, and Inertial Measurement Unit sensor.…”
Section: B the Summer Training Semestermentioning
confidence: 99%
“…Mathematical formulations and explanations were also provided to give students an understanding of the concepts and principles that were necessary for creating these designs. [2] After the mechanical segment of the summer program, students were introduced to robot sensors, sensor implementation and calibration. The sensors covered included the ultrasonic, shaft encoder, touch, line tracking, vision, and Inertial Measurement Unit sensor.…”
Section: B the Summer Training Semestermentioning
confidence: 99%
“…Furthermore, the aims to improve and prepare students who are interested in pursuing a career in engineering for college. [5]…”
Section: Our Rolementioning
confidence: 99%
“…Anwar et al [1] conducted an analysis of 147 studies on educational robotics and found that youth participation in robotics activities enhances their knowledge in STEM fields, their perceived problem-solving abilities, and their interest in pursuing engineering careers. Several outreach programs for both students and teachers have been developed in this regard [2][3][4][5][6][7][8][9]. FIRST® is an example of a program that offers a platform for students to engage in robotics competitions.…”
Section: Introductionmentioning
confidence: 99%
“…Carnegie Mellon University (CMU) offers a robotics education program for middle and high school students utilizing the LEGO® MINDSTORM® NXT/EV3 and TETRIX™ platforms [6][7]. Additionally, many institutions provide robotics summer camps for pre-college students, with various focuses on mechanical design, electronics, and coding [8][9].…”
Section: Introductionmentioning
confidence: 99%